Risk Factors for Early Implant Failure in Geriatric Intertrochanteric Fractures Treated with Twin Interlocking Derotation and Compression Screw Cephalomedullary Nail (InterTAN) - Özmen, E; Yağci, T F; Yildirim, A M; Altan, M; Erşen, A; Sağlam, Y (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: Intertrochanteric hip fractures in elderly patients are a significant cause of morbidity and mortality, with increasing incidence due to the aging population. Despite advancements in intramedullary nailing (IMN) technology, fixation failure remains a concern. This study aims to evaluate pre-and postoperative radiographic risk factors for varus collapse in geriatric intertrochanteric fractures treated with twin interlocking derotation and compression screw cephalomedullary nail (InterTAN, Smith & Nephew). MATERIAL AND METHODS: This retrospective study included patients over 60 years with AO 31A1 and 31A2 intertrochanteric femur fractures treated with InterTAN at a tertiary referral center from August 2012 to August 2017. Patients with high-energy fractures, AO 31A3 fractures, or those requiring open reduction were excluded. Data on demographics, fracture classification, implant sizes, imaging studies, and follow-up were collected. Radiographic assessments included Chang's medial cortical support concept, tip-apex distance (TAD), calcar-referenced TAD (CalTAD), neck-shaft angles (NSA), and screw placement according to Cleveland zones. Varus collapse was defined as a >5° change in NSA within three months postoperatively. Multivariate logistic regression analysis was used to identify risk factors for varus collapse. RESULTS: The study included 136 patients with a mean age of 79.8 years, of whom 38.2% were male. The early postoperative tipapex distance (TAD) averaged 21.9mm, with 30.1% of patients experiencing varus collapse greater than 5°. Positive medial cortical support (PMCS) or neutral position (NP) type reduction was highly protective against varus collapse (p < 0.001), as well as TAD less than 25mm (p < 0.001). Additionally, the placement of screws in the central-central or central-inferior zones provided a protective effect against varus collapse (p = 0.031). Conversely, having an OTA/AO type A2.2 or A2.3 fracture significantly increased the risk of varus collapse (p = 0.030). Other factors, such as CalTAD and the nail width to medullary canal ratio, did not significantly predict varus collapse (p = 0.831 and p = 0.952, respectively). DISCUSSION: Our findings align with previous studies highlighting TAD and screw placement as critical factors in preventing fixation failure. The protective effect of PMCS or NP reduction and the increased risk associated with OTA/AO type A2.2 and A2.3 fractures are noteworthy. Unlike previous studies, CalTAD was not significantly associated with varus collapse in our cohort. The study underscores the importance of surgical technique and radiographic parameters in optimizing outcomes for elderly patients with intertrochanteric fractures. CONCLUSIONS: In elderly patients treated with InterTAN nails, varus collapse is influenced by fracture type, TAD, reduction quality, and screw placement. Ensuring a TAD <25mm, achieving PMCS or NP reduction, and placing screws in central-central or central-inferior zones are crucial for minimizing varus collapse. These findings highlight the importance of meticulous surgical technique and radiographic assessment in managing intertrochanteric fractures in the elderly. KEY WORDS: hip fractures, intertrochanteric fractures, internal Fixation, geriatrics, cephalomedullary nail.
Keywords: Female; fraktury kyčle; intramedulární fixace fraktury; ženské pohlaví; kostní hřeby; kostní šrouby; lidé; pooperační komplikace; Aged, 80 and over; Risk Factors; Fracture Fixation, Intramedullary; retrospektivní studie; Bone Nails; selhání protézy; Male; Postoperative Complications; Aged; rizikové faktory; lidé středního věku; Bone Screws; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Prosthesis Failure; Hip Fractures; Humans